RISING FOOD POISONING INCIDENTS IN MALAYSIA: PROPOSING STRICTER LEGAL MEASURES AGAINST FOOD TRADERS (UUM Journal of Legal Studies, 2025)
Food poisoning incidents in Malaysia have risen in the past decade, causing illnesses and fatalities to consumers. However, to the best of the authors’ knowledge, no food trader has been prosecuted in a court of law for causing food poisoning despite the existence of relevant legal provisions. Instead of facing prosecution, such food traders are merely issued with compounds and/or temporary closure orders. This study employed a doctrinal research method and analysed relevant legal provisions and regulations under the Food Act 1983, the Penal Code, the Prevention and Control of Infectious Diseases Act 1988, the Food Regulations 1985 and the Food Hygiene Regulations 2009. These legal provisions and regulations were analysed without empirical data. The authors also examined the current approach adopted by the enforcement authorities against food traders causing food poisoning. This study recommends a shift in the legal enforcement approach, envisioning that stricter legal measures will deter the occurrences of food poisoning incidents in Malaysia. As previous research on food safety predominantly investigated from scientific or social science perspectives, this study focuses on the legal perspective, addressing key factors for the lack of prosecution of food traders causing food poisoning and suggesting legislative reforms to enable effective prosecution of food traders by recommending amendments to the country’s current food safety laws.